Financial factors influencing environmental, social and governance ratings of public listed companies in Bursa Malaysia - Md. Mahmudul Alam; Yasmin Mohamad Tahir; Abdulazeez Y. H. Saif-Alyousfi; Wanamina Bostan Ali; Ruhaini Muda; Sabariah Nordin (Cogent Business & Management, 2022)
Environmental, Social and Governance (ESG) ratings are widely recognised methods to assess the sustainability practices of corporations. However, the scores of these ratings are not satisfactory in emerging market economies. This study examines the financial factors that influence ESG ratings regarding public listed companies on the FTSE4 Good Bursa Malaysia Index (F4GBM Index). This paper uses static and dynamic Generalized Method of Moments (GMM) techniques to analyse the data of 31 public listed companies on the F4GBM Index and reported full ESG ratings data for the period 2007-2016. To utilise the maximum number of observations by avoiding the missing data and outlier due to COVID-19, this study applied the sample data up to 2016. Using the two-step system dynamic GMM estimator, such results indicate that highly profitable Malaysian companies enjoy a higher score for ESG overall ratings as well as all three individual ratings. Poorer credit management diminishes the environmental ratings, yet increases overall scores such as the social and governance scores. Companies with higher leverage have a weaker social, governance and overall score, but a higher environmental rating. Finally, companies eliciting a higher sustainable growth rate have weak governance and overall scores. This study provides empirical evidence that will be useful to capital market investors, management teams of these companies and policymakers in their efforts to promote responsible investment in Malaysian public listed companies in line with UN-PRI policy.
Keywords: 650; Malaysia; Bursa Malaysia; ESG rating; F4GBM Index; Public listed firms